PENGKAJIAN STABILISASI TANAH LUNAK DAN GAMBUT DENGAN MENGGUNAKAN CAIRAN E-POROUS - Diah Affandi (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2009)
Soil stabilization has been used for an extensive period. Various soil properties can be improved or alteredby soil stabilization. There are several techniques available by which soil properties like strength,workability, permeability and volume changes can be improved or altered.This paper examines the various techniques for soil stabilization with E-porous liquid .This test will becompared to improvement of technical parameters and physics (compressive strength, permeabilityand specific gravity) resulted by the mixture between soft and peat soil with fluid E porous at apercentage of 200 ml, 300 ml, 400 ml and 500 ml.